Classical Archaeology and Political History: Scope for Rapprochement?’ - Morgan, Catherine (Classica et Mediaevalia, 2026)
This article assesses the legacy of the Copenhagen Polis Centre and its influence on the study of Greek social and political organization. The Inventory of Archaic and Classical Poleis transformed the field through its systematic mapping of poleis, horizontal networks, and forms of dependency. Yet its temporal limits and text-centred approach constrained the integration of archaeological evidence into broader narratives of state formation. Building on the CPC’s work and subsequent insights into federalism and regional diversity, I identify five themes – trust, warfare, economic processes, population, and the nature of koina and komai – where archaeology has the potential to reshape understanding of long-term trajectories. Using examples from northwestern Greece, I argue for methodologically ambitious, multi-scalar research capable of addressing structural questions about governance, identity, and political integration. A renewed, theoretically grounded collaboration between archaeology and history that mirrors Mogens Hansen’s comparative vision would expand the possibilities for writing political history through material culture.